2004
DOI: 10.4049/jimmunol.172.4.2286
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T Cells Regulate CD8+ T Cell-Mediated Cutaneous Immune Responses by Restricting Effector T Cell Development through a Fas Ligand-Dependent Mechanism

Abstract: The magnitude and duration of CD8+ T cell-mediated responses in the skin to hapten sensitization and challenge, contact hypersensitivity (CHS), is negatively regulated by CD4+ T cells through an unknown mechanism. In this study we show that CD4+ T cells restrict the development and expansion of hapten-specific CD8+ T cells mediating CHS responses to 2,4-dinitrofluorobenzene. In the absence of CD4+ T cells, high numbers of hapten-specific CD8+ T cells producing IFN-γ were detected in the skin-draining lymph nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 37 publications
5
53
0
1
Order By: Relevance
“…Recently it has been shown that CD47 enhances Fas-mediated cytotoxicity (14). Our data fit well with these results because it is likely that the absence of CD47 might, on the one hand, suppress BNIP-3 up-regulation and thus susceptibility to activation-induced cell death and, on the other, decrease Fas-dependent mechanisms involved in cutaneous hypersensitivity (58,59). Notably, these two mechanisms are not mutually exclusive but might take place simultaneously in the model we describe here.…”
Section: Discussionsupporting
confidence: 78%
“…Recently it has been shown that CD47 enhances Fas-mediated cytotoxicity (14). Our data fit well with these results because it is likely that the absence of CD47 might, on the one hand, suppress BNIP-3 up-regulation and thus susceptibility to activation-induced cell death and, on the other, decrease Fas-dependent mechanisms involved in cutaneous hypersensitivity (58,59). Notably, these two mechanisms are not mutually exclusive but might take place simultaneously in the model we describe here.…”
Section: Discussionsupporting
confidence: 78%
“…Additional work will be required to clarify the role of CD43 in CD8 ϩ T cell migration. Among CD4 ϩ T cells, a population that negatively regulates CHS responses has been reported (33,34). The observation that ear swelling is normal in DKO mice, despite the reduced CD4 ϩ T cell infiltration into the inflamed ear, may suggest that PSGL-1 and CD43 are also involved in the infiltration of these regulatory CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 95%
“…En dehors de l'IL-10, d'autres mécanismes de l'effet régulateur des LT CD4 + existent, notamment celui impliquant la sécrétion ou l'excrétion de TGFβ à la membrane des LT à fonctions régulatrices [21]. Par ailleurs, les cellules T CD4 + pourraient réguler la réponse inflammatoire en éliminant les cellules présentant l'haptène dans les ganglions lymphatiques au cours de la phase de sensibilisation, via un mécanisme dépendant de Fas-ligand, limitant ainsi l'activation des LT CD8 + pré-curseurs [22].…”
Section: Revues Synthèseunclassified